Rewire your brain 2.0 : five healthy factors to a better life - Arden, John Boghosian (Jossey-Bass, 2023)
Combat daily stressors and live your life to its fullest In the newly revised Rewire Your Brain 2.0: Five Healthy Factors to a Better Life, distinguished psychologist Dr. John B. Arden delivers an essential discussion of how to apply the latest developments in neuroscience, epigenetics, and immunology to help improve your mood, memory, lives, longevity, and relationships. You'll learn to overcome mild depression and anxiety, procrastination, burnout, compassion fatigue, and a variety of other negative thought patterns. You'll also find: Practical, self-help tips based on well-researched principles that are proven to work in the real world Ways to minimize the impact of everyday anxiety, stress, and depression and live your life to its fullest Tactics for improving your memory for day-to-day tasks at work and at home A practical and hands-on roadmap to applying new advances in neuroscience, psychology, gene expression, and immune system research to everyday problems we all face, Rewire Your Brain 2.0 deserves a place on the bookshelves of professionals, athletes, parents, and anyone else susceptible to the stressors of daily life.